Active energy beam curable resin composition, cured film and article
Patent Information
- Application Number
- KR1020247010310
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-12-23
- Filing Date
- 2022-12-01
- Publication Date
- 2026-09-16
- Estimated Expiration
- 2042-12-01
Smart Images

Figure 112024034251601-PCT00001 
Figure 112024034251601-PCT00002 
Figure 112024034251601-PCT00003
Abstract
Description
Technology Field
[0001] The present invention relates to an active energy beam curable resin composition, a cured film, and an article. Background Technology
[0002] Recently, thermoplastic resin materials, represented by plastics, are widely used in fields ranging from construction to the automotive industry due to their excellent lightweight properties, impact resistance, processability, and recyclability. However, because they face challenges such as poor weather resistance, stain resistance, heat resistance, solvent resistance, and yellowing resistance, they are often used with a coating layer to supplement their performance.
[0003] As such a coating layer, it has been proposed to use an ultraviolet curable resin composition containing an inorganic-organic composite resin (see, for example, Patent Document 1). This ultraviolet curable resin composition contains a composite resin having polysiloxane segments and vinyl polymer segments, but although it has excellent weather resistance, heat resistance, solvent resistance, and scratch resistance, it has poor substrate adherence, so there were problems such as cracking during processing with high design quality or processing after painting. Prior art literature
[0004] Japanese Publication No. 2006-328354 The problem to be solved
[0005] The problem that the present invention aims to solve is to provide an active energy beam curable resin composition, a cured film, and an article capable of forming a film with excellent film appearance, adhesion, solvent resistance, scratch resistance, weather resistance, stain resistance, and processability. means of solving the problem
[0006] The inventors, having conducted diligent research to solve the above problem, discovered that the problem can be solved by using an active energy beam curable resin composition containing a specific composite resin, a specific acrylate (meth)acrylate resin, and a photopolymerization initiator, thereby completing the present invention.
[0007] That is, the present invention relates to an active energy beam curable resin composition, a cured film, and an article, wherein the composition comprises a composite resin (A), an acrylic (meth)acrylate resin (B), and a photopolymerization initiator (C), wherein the composite resin (A) is formed by a structural unit represented by general formula (1) and / or general formula (2), a polysiloxane segment (a1) having a silanol group and / or a hydrolyzable silyl group, and a vinyl polymer segment (a2) are bonded by a bond represented by general formula (3), and the weight average molecular weight of the acrylic (meth)acrylate resin (B) is 10,000 to 70,000.
[0008]
[0009]
[0010] (of general formulas (1) and (2), R 1 , R 2 and R 3 une, each independently, -R 4 -CH=CH2, -R 4 -C(CH3)=CH2, -R 4 -O-CO-C(CH3)=CH2, and -R 4 A group having one polymerizable double bond selected from the group consisting of -O-CO-CH=CH2 (where R 4 represents a single bond or an alkylene group having 1 to 6 carbon atoms), an alkyl group having 1 to 6 carbon atoms, a cycloalkyl group having 3 to 8 carbon atoms, an aryl group, or an aralkyl group having 7 to 12 carbon atoms)
[0011]
[0012] (In the general formula (3), the carbon atoms constitute a part of the vinyl polymer segment (a2), and the silicon atoms bonded only to oxygen atoms constitute a part of the polysiloxane segment (a1).) Effects of the invention
[0013] The active energy beam curable resin composition of the present invention can be used as a coating agent or an adhesive, in that it is capable of forming a cured film with excellent film appearance, adhesion, solvent resistance, scratch resistance, weather resistance, stain resistance, and processability, and can be particularly well used as a coating agent. Specific details for implementing the invention
[0014] The active energy beam curable resin composition of the present invention is an active energy beam curable resin composition comprising a composite resin (A), an acrylate (meth)acrylate resin (B), and a photopolymerization initiator (C), wherein the composite resin (A) comprises a structural unit represented by general formula (1) and / or general formula (2), a polysiloxane segment (a1) having a silanol group and / or a hydrolyzable silyl group, and a vinyl polymer segment (a2) bonded by a bond represented by general formula (3), and the weight average molecular weight of the acrylate (meth)acrylate resin (B) is 10,000 to 70,000.
[0015] The above composite resin (A) is a composite resin in which a structural unit represented by the above general formula (1) and / or the above general formula (2), a polysiloxane segment (a1) having a silanol group and / or a hydrolyzable silyl group (hereinafter referred to simply as polysiloxane segment (a1)), and a vinyl polymer segment (a2) having an alcoholic hydroxyl group (hereinafter referred to simply as vinyl polymer segment (a2)) are bonded by a bond represented by the above general formula (3).
[0016] The silanol group and / or hydrolyzable silyl group of the polysiloxane segment (a1) described later and the silanol group and / or hydrolyzable silyl group of the vinyl polymer segment (a2) described later undergo a dehydration condensation reaction to form a bond represented by the general formula (3). Accordingly, in the general formula (3), the carbon atom constitutes a part of the vinyl polymer segment (a2), and the silicon atom bonded only to the oxygen atom constitutes a part of the polysiloxane segment (a1).
[0017] The form of the composite resin (A) may include, for example, a composite resin having a graft structure in which the polysiloxane segment (a1) is chemically bonded as a side chain of the polymer segment (a2), or a composite resin having a block structure in which the polymer segment (a2) and the polysiloxane segment (a1) are chemically bonded.
[0018] The above polysiloxane segment (a1) is a segment having a structural unit represented by general formula (1) and / or general formula (2) and a silanol group and / or a hydrolyzable silyl group. Among the structural units represented by general formula (1) and / or general formula (2), there are groups having polymerizable double bonds.
[0019] The structural unit represented by the above general formula (1) and / or the above general formula (2) has a group having a polymerizable double bond as an essential component.
[0020] Specifically, R in the above general formulas (1) and (2) 1 , R 2 and R 3 une, each independently, -R 4 -CH=CH2, -R 4 -C(CH3)=CH2, -R 4 -O-CO-C(CH3)=CH2, and -R 4 A group having one polymerizable double bond selected from the group consisting of -O-CO-CH=CH2 (where R 4represents a single bond or an alkylene group having 1 to 6 carbon atoms), an alkyl group having 1 to 6 carbon atoms, a cycloalkyl group having 3 to 8 carbon atoms, an aryl group, or an aralkyl group having 7 to 12 carbon atoms, and R 1 , R 2 and R 3 At least one of is a group having the polymerizable double bond. Also, the R 4 As the above alkylene group having 1 to 6 carbon atoms, for example, a methylene group, an ethylene group, a propylene group, an isopropylene group, a butylene group, an isobutylene group, a sec-butylene group, a tert-butylene group, a pentylene group, an isopentylene group, a neopentylene group, a tert-pentylene group, 1-methylbutylene group, 2-methylbutylene group, 1,2-dimethylpropylene group, 1-ethylpropylene group, a hexylene group, an isohexylene group, 1-methylpentylene group, 2-methylpentylene group, 3-methylpentylene group, 1,1-dimethylbutylene group, 1,2-dimethylbutylene group, 2,2-dimethylbutylene group, 1-ethylbutylene group, 1,1,2-trimethylpropylene group, 1,2,2-trimethylpropylene group, Examples include 1-ethyl-2-methylpropylene groups, 1-ethyl-1-methylpropylene groups, etc. Among these, R 4 In terms of ease of obtaining raw materials, a single bond or an alkylene group having 2 to 4 carbon atoms is preferred.
[0021] In addition, examples of the above alkyl groups having 1 to 6 carbon atoms include methyl, ethyl, propyl, isopropyl, butyl, isobutyl, sec-butyl, tert-butyl, pentyl, isopentyl, neopentyl, tert-pentyl, 1-methylbutyl, 2-methylbutyl, 1,2-dimethylpropyl, 1-ethylpropyl, hexyl, isohexyl, 1-methylpentyl, 2-methylpentyl, 3-methylpentyl, 1,1-dimethylbutyl, 1,2-dimethylbutyl, 2,2-dimethylbutyl, 1-ethylbutyl, 1,1,2-trimethylpropyl, 1,2,2-trimethylpropyl, 1-ethyl-2-methylpropyl, 1-ethyl-1-methylpropyl, etc.
[0022] In addition, examples of the cycloalkyl group having 3 to 8 carbon atoms include a cyclopropyl group, a cyclobutyl group, a cyclopentyl group, a cyclohexyl group, etc. In addition, examples of the aryl group include a phenyl group, a naphthyl group, a 2-methylphenyl group, a 3-methylphenyl group, a 4-methylphenyl group, a 4-vinylphenyl group, a 3-isopropylphenyl group, etc.
[0023] In addition, examples of the above aralkyl groups having 7 to 12 carbon atoms include benzyl groups, diphenylmethyl groups, naphthylmethyl groups, etc.
[0024] Also, R 1 , R 2 and R 3 The statement that at least one of the groups having the polymerizable double bond is, specifically, that when the polysiloxane segment (a1) has only a structural unit represented by the general formula (1), R 1 This is a group having the above-mentioned polymerizable double bond, and in the case where the polysiloxane segment (a1) has only a structural unit represented by the general formula (2), R 2 and / or R 3 This is a group having the above-mentioned polymerizable double bond, and if the polysiloxane segment (a1) has both structural units represented by general formula (1) and general formula (2), R 1 , R 2 and R 3 It indicates that at least one of them is a cause having a polymerizable double bond.
[0025] It is preferable that two or more of the above polymerizable double bonds exist in the polysiloxane segment (a1), more preferable that 3 to 200 exist, and more preferable that 3 to 50 exist, thereby obtaining a coating film with excellent durability. Specifically, if the content of the polymerizable double bonds in the above polysiloxane segment (a1) is 3 to 35 weight percent, the desired weather resistance and adhesion can be obtained. Also, the term "polymerizable double bond" as used herein refers to a general term for groups among vinyl groups, vinylidene groups, or vinylene groups that can undergo a growth reaction by free radicals. Furthermore, the content of the polymerizable double bonds refers to the weight percent in the polysiloxane segment of said vinyl group, vinylidene group, or vinylene group.
[0026] As a group having a polymerizable double bond, any known functional group comprising the vinyl group, vinylidene group, or vinylene group may be used, but among them, -R 4 -C(CH3)=CH2 or -R 4 The (meth)acryloyl group represented as -O-CO-C(CH3)=CH2 is preferred because it is highly reactive during UV curing, has good compatibility with the vinyl polymer segment (a2) described later, and provides a cured film with excellent transparency.
[0027] The structural unit represented by the above general formula (1) and / or the above general formula (2) is a three-dimensional network polysiloxane structural unit in which two or three of the silicon bonds are involved in crosslinking. Since it forms a three-dimensional network structure but does not form a dense network structure, it does not cause gelation during manufacturing or primer formation, and storage stability is also good.
[0028] In the present invention, a silanol group is a silicon-containing group having a hydroxyl group directly bonded to a silicon atom. Specifically, the silanol group is preferably a silanol group formed by bonding an oxygen atom having a bonded number to a hydrogen atom, of a structural unit represented by the general formula (1) and / or the general formula (2).
[0029] In addition, the hydrolyzable silyl group in the present invention is a silicon-containing group having a hydrolyzable group directly bonded to a silicon atom, and specifically, for example, a group represented by the general formula (4).
[0030]
[0031] (In general formula (4), R 5 is a monovalent organic group such as an alkyl group, aryl group, or aralkyl group, R 6 b is a hydrolyzable group selected from the group consisting of a halogen atom, an alkoxy group, an acyloxy group, a phenoxy group, an aryloxy group, a mercapto group, an amino group, an amide group, an aminooxy group, an iminooxy group, and an alkenyloxy group. Also, b is an integer from 0 to 2.
[0032] The above R 5 Examples of alkyl groups include, for instance, methyl group, ethyl group, propyl group, isopropyl group, butyl group, isobutyl group, sec-butyl group, tert-butyl group, pentyl group, isopentyl group, neopentyl group, tert-pentyl group, 1-methylbutyl group, 2-methylbutyl group, 1,2-dimethylpropyl group, 1-ethylpropyl group, hexyl group, isohexyl group, 1-methylpentyl group, 2-methylpentyl group, 3-methylpentyl group, 1,1-dimethylbutyl group, 1,2-dimethylbutyl group, 2,2-dimethylbutyl group, 1-ethylbutyl group, 1,1,2-trimethylpropyl group, 1,2,2-trimethylpropyl group, 1-ethyl-2-methylpropyl group, 1-ethyl-1-methylpropyl group, etc.
[0033] In addition, examples of aryl groups include phenyl groups, naphthyl groups, 2-methylphenyl groups, 3-methylphenyl groups, 4-methylphenyl groups, 4-vinylphenyl groups, 3-isopropylphenyl groups, etc.
[0034] In addition, examples of aryl groups include benzyl groups, diphenylmethyl groups, naphthylmethyl groups, etc.
[0035] The above R 6 In this case, halogen atoms include, for example, fluorine atoms, chlorine atoms, bromine atoms, iodine atoms, etc.
[0036] Examples of alkoxy groups include methoxy groups, ethoxy groups, propoxy groups, isopropoxy groups, butoxy groups, second butoxy groups, third butoxy groups, etc.
[0037] In addition, examples of acyloxy groups include formyloxy, acetoxy, propanoyloxy, butanoyloxy, pivaloyloxy, pentanoyyloxy, phenylacetoxy, acetoacetoxy, benzoyyloxy, naphtoyloxy, etc.
[0038] In addition, examples of aryloxy groups include phenyloxy and naphthyloxy.
[0039] Examples of alkenyloxy groups include vinyloxy groups, allyloxy groups, 1-propenyloxy groups, isopropenyloxy groups, 2-butenyloxy groups, 3-butenyloxy groups, 2-pentenyloxy groups, 3-methyl-3-butenyloxy groups, 2-hexenyloxy groups, etc.
[0040] The above R 6 As the hydrolyzable group represented by [ ] is hydrolyzed, the hydrolyzable silyl group represented by the general formula (4) becomes a silanol group. Among these, the methoxy group and the ethoxy group are preferred due to their excellent hydrolytic properties.
[0041] In addition, the hydrolyzable silyl group is preferably, specifically, a hydrolyzable silyl group in which an oxygen atom having a bonded number of structural units represented by the general formula (1) and / or the general formula (2) is bonded to or substituted for the hydrolyzable group.
[0042] When forming a coating film by a curing reaction of the group having the polymerizable double bond, the above silanol group or the above hydrolyzable silyl group undergoes a hydrolytic condensation reaction in parallel with the curing reaction between the hydroxyl group in the silanol group and the hydrolyzable group in the hydrolyzable silyl group, so that the crosslinking density of the polysiloxane structure of the resulting coating film is increased, and a coating film with excellent solvent resistance can be formed.
[0043] In addition, it is used when combining a polysiloxane segment (a1) containing the above silanol group or the above hydrolyzable silyl group and a vinyl polymer segment (a2) described later by interposing a bond represented by the above general formula (3).
[0044] The polysiloxane segment (a1) is not particularly limited except that it has a structural unit represented by the general formula (1) and / or the general formula (2) and a silanol group and / or a hydrolyzable silyl group, and may include other groups. For example,
[0045] R in the above general formula (1) 1 The above-mentioned structural unit having a polymerizable double bond and R in the above general formula (1) 1 It may be a polysiloxane segment (a1) in which structural units such as alkyl groups, such as methyl, coexist, and
[0046] R in the above general formula (1) 1 The above-mentioned structural unit having a polymerizable double bond and R in the above general formula (1) 1 This structural unit, which is an alkyl group such as a methyl group, and R in the general formula (2) 2 and R 3 It may be a polysiloxane segment (a1) in which structural units such as alkyl groups, such as methyl groups, coexist, and
[0047] R in the above general formula (1) 1 The above-mentioned structural unit having a polymerizable double bond and R in the above general formula (2) 2 and R 3It may be a polysiloxane segment (a1) in which structural units such as alkyl groups, such as methyl groups, coexist, and there are no particular limitations.
[0048] Specifically, the polysiloxane segment (a1) may be, for example, have the following structure.
[0049]
[0050]
[0051]
[0052]
[0053]
[0054]
[0055]
[0056]
[0057]
[0058] The above vinyl polymer segment (a2) is a vinyl polymer segment such as an acrylic polymer, a fluoroolefin polymer, a vinyl ester polymer, an aromatic vinyl polymer, or a polyolefin polymer, and among them, an acrylic polymer segment is preferred in that the transparency and gloss of the resulting coating film are excellent.
[0059] The above acrylic polymerizable segment is obtained by polymerizing or copolymerizing a general-purpose (meth)acrylic monomer. There are no particular limitations on the (meth)acrylic monomer, and vinyl monomers can also be copolymerized. For example, alkyl (meth)acrylates having an alkyl group with 1 to 22 carbon atoms, such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and lauryl (meth)acrylate; aralkyl (meth)acrylates, such as benzyl (meth)acrylate and 2-phenylethyl (meth)acrylate; Cycloalkyl (meth)acrylates such as cyclohexyl (meth)acrylate and isobornyl (meth)acrylate; ω-alkoxyalkyl (meth)acrylates such as 2-methoxyethyl (meth)acrylate and 4-methoxybutyl (meth)acrylate; aromatic vinyl monomers such as styrene, p-tert-butylstyrene, α-methylstyrene, and vinyltoluene; vinyl carboxylate esters such as vinyl acetate, vinyl propionate, vinyl pivalate, and vinyl benzoate; alkyl esters of crotonic acids such as methyl crotonicate and ethyl crotonicate; dialkyl esters of unsaturated dibasic acids such as dimethyl maleate, di-n-butyl maleate, dimethyl fumarate, and dimethyl itaconate; α-olefins such as ethylene and propylene; Examples include fluoroolefins such as vinylidene fluoride, tetrafluoroethylene, hexafluoropropylene, and chlorotrifluoroethylene; alkyl vinyl ethers such as ethyl vinyl ether and n-butyl vinyl ether; cycloalkyl vinyl ethers such as cyclopentyl vinyl ether and cyclohexyl vinyl ether; and tertiary amide group-containing monomers such as N,N-dimethyl(meth)acrylamide, N-(meth)acryloylmorpholine, N-(meth)acryloylpyrrolidine, and N-vinylpyrrolidone.
[0060] In addition, the vinyl polymer segment (a2) is more preferably a (meth)acrylic repeating unit having a cyclic hydrocarbon group to improve adhesion to the plastic substrate. Preferably, the (meth)acrylic repeating unit having a cyclic hydrocarbon group may be a (meth)acrylate having a cyclic hydrocarbon group, such as cyclohexyl (meth)acrylate, cyclofentanyl (meth)acrylate, adamantyl (meth)acrylate, tricyclodecanyl (meth)acrylate, tetracyclododecanyl (meth)acrylate, dicyclofentanyl (meth)acrylate, isobornyl acrylate, etc. These may be used individually or in combination of two or more types.
[0061] There are no particular limitations on the polymerization method, solvent, or polymerization initiator when copolymerizing the above monomers, and a vinyl polymer segment (a2) can be obtained by known methods. For example, a vinyl polymer segment (a2) can be obtained by various polymerization methods such as bulk radical polymerization, solution radical polymerization, and non-water dispersed radical polymerization, using polymerization initiators such as 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2-methylbutyronitrile), tert-butylperoxypivalate, tert-butylperoxybenzoate, tert-butylperoxy-2-ethylhexanoate, di-tert-butylperoxide, cumene hydroperoxide, and diisopropyl peroxycarbonate.
[0062] The number average molecular weight of the vinyl polymer segment (a2) is preferably 500 to 200,000 when converted to the number average molecular weight (hereinafter abbreviated as Mn), which can prevent thickening or gelation when manufacturing the composite resin (A) and also provides excellent durability. Among these, a range of 700 to 100,000 Mn is more preferable, and 1,000 to 50,000 is more preferable for reasons of coating suitability and adhesion to the substrate described later.
[0063] Additionally, the vinyl polymer segment (a2) has silanol groups and / or hydrolyzable silyl groups directly bonded to carbon bonds within the vinyl polymer segment (a2) in order to form a composite resin (A) bonded to the polysiloxane segment (a1) by a bond represented by the general formula (3). Since these silanol groups and / or hydrolyzable silyl groups become bonds represented by the general formula (3) during the manufacture of the composite resin (A) described later, they are almost non-existent in the vinyl polymer segment (a2) of the final product, the composite resin (A). However, there is no problem even if silanol groups and / or hydrolyzable silyl groups remain in the vinyl polymer segment (a2), and when forming a coating film by curing reaction of the group having the polymerizable double bond, a hydrolytic condensation reaction proceeds between the hydroxyl groups in the silanol groups and the hydrolyzable groups in the hydrolyzable silyl groups in parallel with the curing reaction, so the crosslinking density of the polysiloxane structure of the resulting coating film is increased, and a coating film with excellent durability can be formed.
[0064] A vinyl polymer segment (a2) having a silanol group and / or a hydrolyzable silyl group directly bonded to a carbon bond is, specifically, obtained by copolymerizing the general-purpose monomer and a vinyl monomer containing a silanol group and / or a hydrolyzable silyl group directly bonded to a carbon bond.
[0065] Examples of vinyl monomers containing silanol groups and / or hydrolyzable silyl groups directly bonded to carbon bonds include vinyltrimethoxysilane, vinyltriethoxysilane, vinylmethyldimethoxysilane, vinyltri(2-methoxyethoxy)silane, vinyltriacetoxysilane, vinyltrichlorosilane, 2-trimethoxysilylethylvinyl ether, 3-(meth)acryloyloxypropyltrimethoxysilane, 3-(meth)acryloyloxypropyltriethoxysilane, 3-(meth)acryloyloxypropylmethyldimethoxysilane, 3-(meth)acryloyloxypropyltrichlorosilane, etc. Among these, vinyltrimethoxysilane and 3-(meth)acryloyloxypropyltrimethoxysilane are preferred in that they allow for easy hydrolysis reaction and also allow for easy removal of by-products after the reaction.
[0066] In addition, when containing the polyisocyanate described below, it is preferable that the vinyl polymer segment (a2) has an alcoholic hydroxyl group. The vinyl polymer segment (a2) having an alcoholic hydroxyl group can be obtained by copolymerizing a (meth)acrylic monomer having an alcoholic hydroxyl group. As (meth)acrylic monomers having alcoholic hydroxyl groups, specifically, various α, β-ethyl(meth)acrylate, 2-hydroxypropyl(meth)acrylate, 3-hydroxypropyl(meth)acrylate, 2-hydroxybutyl(meth)acrylate, 3-hydroxybutyl(meth)acrylate, 4-hydroxybutyl(meth)acrylate, 3-chloro-2-hydroxypropyl(meth)acrylate, di-2-hydroxyethyl fumarate, mono-2-hydroxyethyl monobutyl fumarate, polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, and "Fraxel FM or Fraxel FA" [caprolactone addition monomer manufactured by Daicel Kagaku Co., Ltd.] Examples include hydroxyalkyl esters of unsaturated carboxylic acids, or adducts thereof with ε-caprolactone. Among these, 2-hydroxyethyl (meth)acrylate is preferred because it reacts easily.
[0067] It is preferable to determine the above alcoholic hydroxyl group amount by calculating it from the amount of polyisocyanate added as described below.
[0068] In addition, as described below, in the present invention, it is more preferable to use an active energy beam curable monomer having an alcoholic hydroxyl group. Accordingly, the amount of alcoholic hydroxyl groups in the vinyl polymer segment (a2) having an alcoholic hydroxyl group can be determined by adding the amount of the active energy beam curable monomer having an alcoholic hydroxyl group used in combination. Substantially, it is preferable to contain it in the range of 30 to 300 when converted to the hydroxyl value of the vinyl polymer segment (a2).
[0069] The above composite resin (A) is specifically manufactured by the methods shown in (Method 1) to (Method 3) below.
[0070] (Method 1) A vinyl monomer containing a silanol group and / or a hydrolyzable silyl group directly bonded to a carbon bond is copolymerized with the above general-purpose (meth)acrylic monomer, etc., to obtain a vinyl polymer segment (a2) containing a silanol group and / or a hydrolyzable silyl group directly bonded to a carbon bond. To this, a silane compound having a silanol group and / or a hydrolyzable silyl group and a polymerizable double bond, and a general-purpose silane compound are mixed, if necessary, and a hydrolytic condensation reaction is carried out.
[0071] In the method, the silanol group and / or hydrolyzable silyl group of a silane compound having a silanol group and / or hydrolyzable silyl group and a polymerizable double bond, and the silanol group and / or hydrolyzable silyl group of a vinyl polymer segment (a2) having a silanol group and / or hydrolyzable silyl group directly bonded to a carbon bond are subjected to a hydrolytic condensation reaction to form the polysiloxane segment (a1), and a composite resin (A) is obtained in which the polysiloxane segment (a1) and the vinyl polymer segment (a2) are combined by a bond represented by the general formula (3).
[0072] (Method 2) In the same manner as in Method 1, a vinyl polymer segment (a2) containing a silanol group and / or a hydrolyzable silyl group directly bonded to a carbon bond is obtained.
[0073] Meanwhile, a polysiloxane segment (a1) is obtained by hydrolyzing and condensing a silane compound having a silanol group and / or a hydrolyzable silyl group and a polymerizable double bond, or, if necessary, a general-purpose silane compound. Then, a hydrolyzing and condensing reaction is performed between the silanol group and / or a hydrolyzable silyl group of the vinyl polymer segment (a2) and the silanol group and / or a hydrolyzable silyl group of the polysiloxane segment (a1).
[0074] (Method 3) Similar to Method 1, a vinyl polymer segment (a2) containing a silanol group and / or a hydrolyzable silyl group directly bonded to a carbon bond is obtained. Meanwhile, a polysiloxane segment (a1) is obtained in the same manner as in Method 2. Additionally, a silane compound containing a silane compound having a polymerizable double bond is mixed with, if necessary, a general-purpose silane compound, and subjected to a hydrolytic condensation reaction.
[0075] In addition, as general-purpose silane compounds used in the above (Method 1) to (Method 3), for example, various organotrialkoxysilanes such as methyltrimethoxysilane, methyltriethoxysilane, methyltri-n-butoxysilane, ethyltrimethoxysilane, n-propyltrimethoxysilane, iso-butyltrimethoxysilane, cyclohexyltrimethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, etc.; various diorganodialkoxysilanes such as dimethyldimethoxysilane, dimethyldiethoxysilane, dimethyldi-n-butoxysilane, diethyldimethoxysilane, diphenyldimethoxysilane, methylcyclohexyldimethoxysilane, or methylphenyldimethoxysilane; Examples of chlorosilanes include methyltrichlorosilane, ethyltrichlorosilane, phenyltrichlorosilane, vinyltrichlorosilane, dimethyldichlorosilane, diethyldichlorosilane, or diphenyldichlorosilane. Among these, organotrialkoxysilane or diorganodialkoxysilane is preferred as it allows the hydrolysis reaction to proceed easily and also enables the easy removal of by-products after the reaction.
[0076] In addition, tetrafunctional alkoxysilane compounds such as tetramethoxysilane, tetraethoxysilane, or tetran-propoxysilane, or partial hydrolysis condensates of said tetrafunctional alkoxysilane compounds, may be used in combination within a range that does not impair the effects of the present invention. When using said tetrafunctional alkoxysilane compounds or their partial hydrolysis condensates in combination, it is preferable to use them in combination such that the silicon atoms of said tetrafunctional alkoxysilane compounds do not exceed 20 mol% with respect to all silicon atoms constituting the polysiloxane segment (a1).
[0077] In addition, metal alkoxide compounds other than silicon atoms, such as boron, titanium, zirconium, or aluminum, may be used in combination with the above silane compound to the extent that the effects of the present invention are not impaired. For example, it is preferable to use them in combination so that the metal atoms of the metal alkoxide compound described above do not exceed 25 mol% with respect to all silicon atoms constituting the polysiloxane segment (a1).
[0078] The hydrolysis condensation reaction in the above (Method 1) to (Method 3) refers to a condensation reaction in which a portion of the hydrolyzable group is hydrolyzed by the influence of water or the like to form a hydroxyl group, and subsequently proceeds between the said hydroxyl groups or between the said hydroxyl group and the hydrolyzable group. Although the hydrolysis condensation reaction can be carried out by known methods, it is preferable to carry out the reaction by supplying water and a catalyst in the above manufacturing process as it is simpler.
[0079] As catalysts to be used, for example, inorganic acids such as hydrochloric acid, sulfuric acid, and phosphoric acid; organic acids such as p-toluenesulfonic acid, monoisopropyl phosphate, and acetic acid; inorganic bases such as sodium hydroxide or potassium hydroxide; titanate esters such as tetraisopropyl titanate and tetrabutyl titanate; and various compounds containing basic nitrogen atoms such as 1,8-diazabicyclo[5.4.0]undecene-7 (DBU), 1,5-diazabicyclo[4.3.0]nonene-5 (DBN), 1,4-diazabicyclo[2.2.2]octane (DABCO), tri-n-butylamine, dimethylbenzylamine, monoethanolamine, imidazole, and 1-methylimidazole; Examples include various quaternary ammonium salts such as tetramethylammonium salt, tetrabutylammonium salt, and dilauryldimethylammonium salt, and quaternary ammonium salts having chloride, bromide, carboxylate, or hydroxyoxide as a counter anion; and tin carboxylates such as dibutyltin diacetate, dibutyltin dioctoeate, dibutyltin dilaurate, dibutyltin diacetylacetonate, tin octylate, or tin stearate. The catalyst may be used alone or in combination of two or more types.
[0080] Although there is no particular limitation on the amount of the catalyst added, generally, it is preferable to use it in the range of 0.0001 to 10 weight% with respect to the total amount of each compound having a silanol group or a hydrolyzable silyl group, more preferable to use it in the range of 0.0005 to 3 weight%, and particularly preferable to use it in the range of 0.001 to 1 weight%.
[0081] In addition, the amount of water supplied is preferably 0.05 moles or more, more preferably 0.1 moles or more, and particularly preferably 0.5 moles or more per 1 mole of the silanol group or hydrolyzable silyl group of each compound having the silanol group or hydrolyzable silyl group.
[0082] These catalysts and water may be supplied in a batch or sequentially, and a pre-mixed mixture of catalyst and water may also be supplied.
[0083] When carrying out the hydrolysis condensation reaction in the above (Method 1) to (Method 3), the reaction temperature is appropriately in the range of 0°C to 150°C, and preferably within the range of 20°C to 100°C. In addition, the reaction pressure can be carried out under any condition, such as atmospheric pressure, pressurized pressure, or reduced pressure. Furthermore, alcohol or water, which are by-products that may be generated in the above hydrolysis condensation reaction, may be removed by methods such as distillation as necessary.
[0084] The input ratio of each compound in the above (Method 1) to (Method 3) is appropriately selected according to the structure of the composite resin (A) used in the present invention. Among these, in order to ensure excellent durability of the resulting coating film, it is preferable to obtain a composite resin (A) such that the content of the polysiloxane segment (a1) is 30 to 95 weight%, and 50 to 95 weight% is more preferable.
[0085] In the above (Method 1) to (Method 3), a specific method for compounding a polysiloxane segment and a vinyl polymer segment into a block structure may be provided by using a vinyl polymer segment having a structure having the above-mentioned silanol group and / or hydrolyzable silyl group only at one or both ends of the polymer chain as an intermediate, and, for example, in (Method 1), a silane compound having a silanol group and / or hydrolyzable silyl group and a polymerizable double bond, and if necessary, a general-purpose silane compound, mixed with the vinyl polymer segment and subjected to a hydrolytic condensation reaction.
[0086] Meanwhile, in the above (Method 1) to (Method 3), as a specific method for grafting a polysiloxane segment onto a vinyl polymer segment, a vinyl polymer segment having a structure in which the above-mentioned silanol groups and / or hydrolyzable silyl groups are randomly distributed on the main chain of the vinyl polymer segment is used as an intermediate, and for example, in (Method 2), a method of hydrolyzing and condensing the silanol groups and / or hydrolyzable silyl groups of the vinyl polymer segment and the above-mentioned silanol groups and / or hydrolyzable silyl groups of the polysiloxane segment may be used.
[0087] In the case where the vinyl polymer segment (a2) in the above composite resin (A) has an alcoholic hydroxyl group, it is preferable to use polyisocyanate in combination, and in that case, it is preferable to include 5 to 50 weight percent of the polyisocyanate relative to the total solid content of the active energy beam curable resin layer. By including polyisocyanate in this range, a coating film with particularly excellent long-term weather resistance (specifically, crack resistance) is obtained, especially in the outdoor environment. This is presumed to be because the polyisocyanate reacts with the hydroxyl group in the system (which is the hydroxyl group in the vinyl polymer segment (a2) or the hydroxyl group in the active energy beam curable monomer having the alcoholic hydroxyl group described later), forming a urethane bond in the soft segment, which acts to relieve stress concentration caused by curing derived from polymerizable double bonds.
[0088] There are no particular limitations on the polyisocyanates used, and known ones may be used. However, polyisocyanates made primarily from aromatic diisocyanates such as tolylene diisocyanate and diphenylmethane-4,4'-diisocyanate, or aryl diisocyanates such as meta-xylylene diisocyanate and α,α,α',α'-tetramethyl-meta-xylylene diisocyanate, have a problem in that the cured film turns yellow upon long-term outdoor exposure, so it is desirable to minimize the amount used.
[0089] From the perspective of long-term outdoor use, an aliphatic polyisocyanate having an aliphatic diisocyanate as the main raw material is suitable as the polyisocyanate used in the present invention. Examples of aliphatic diisocyanates include tetramethylene diisocyanate, 1,5-pentamethylene diisocyanate, 1,6-hexamethylene diisocyanate (hereinafter abbreviated as "HDI"), 2,2,4-(or 2,4,4-trimethyl-1,6-hexamethylene diisocyanate, lysine isocyanate, isophorone diisocyanate, hydrogenated xylene diisocyanate, hydrogenated diphenylmethane diisocyanate, 1,4-diisocyanate cyclohexane, 1,3-bis(diisocyanate methyl)cyclohexane, 4,4'-dicyclohexylmethane diisocyanate, etc. Among these, HDI is particularly suitable in terms of crack resistance and cost.
[0090] Examples of aliphatic polyisocyanates obtained from aliphatic diisocyanates include allophanate-type polyisocyanates, biuret-type polyisocyanates, adduct-type polyisocyanates, and isocyanurate-type polyisocyanates, any of which can be appropriately used.
[0091] In addition, as the above-mentioned polyisocyanate, so-called blocked polyisocyanate compounds that have been blocked by various blocking agents may be used. As blocking agents, for example, alcohols such as methanol, ethanol, and lactic acid esters; phenolic hydroxyl group-containing compounds such as phenol and salicylic acid esters; amides such as ε-caprolactam and 2-pyrrolidone; oximes such as acetone oxime and methyl ethyl keto oxime; and active methylene compounds such as methyl acetoacetate, ethyl acetoacetate, and acetylacetone may be used.
[0092] It is preferable that the isocyanate groups in the above polyisocyanate be 3 to 30 weight percent in terms of crack resistance and wear resistance of the resulting cured film. If the isocyanate groups in the above polyisocyanate exceed 30%, the molecular weight of the polyisocyanate decreases, and there is a risk that crack resistance due to stress relaxation will not be exhibited. The reaction between the polyisocyanate and the hydroxyl groups in the system (which are hydroxyl groups in the above vinyl polymer segment (a2) or hydroxyl groups in the above active energy beam curable monomer having alcoholic hydroxyl groups described later) does not particularly require heating, and, for example, if the curing form is ultraviolet, the reaction proceeds slowly by leaving it at room temperature after coating and UV irradiation. Additionally, if necessary, the reaction between the alcoholic hydroxyl groups and the isocyanate may be accelerated by heating at 80°C for several minutes to several hours (20 minutes to 4 hours) after UV irradiation. In that case, a known urethane catalyst may be used as needed. The urethane catalyst is appropriately selected according to the desired reaction temperature.
[0093] As for the above acrylic (meth)acrylate resin (B), for example, it may be obtained by introducing (meth)acryloyl groups by further reacting (meth)acrylate monomer (β) having functional groups capable of reacting with said reactive functional groups with an acrylic resin intermediate obtained by polymerizing (meth)acrylate monomer (α) having reactive functional groups such as hydroxyl groups, carboxyl groups, isocyanate groups, and glycidyl groups as essential components.
[0094] In addition, in the present invention, "(meth)acrylate resin" refers to a resin having a (meth)acryloyl group in its molecule, and "(meth)acryloyl group" refers to one or both of an acryloyl group and a methacryloyl group. Furthermore, "(meth)acrylate" refers to one or both of an acrylate and a methacrylate.
[0095] The (meth)acrylate monomer (α) having the above-mentioned reactive functional group may include, for example, a hydroxyl group-containing (meth)acrylate monomer such as hydroxyethyl (meth)acrylate or hydroxypropyl (meth)acrylate; a carboxyl group-containing (meth)acrylate monomer such as (meth)acrylic acid; an isocyanate group-containing (meth)acrylate monomer such as 2-acryloyloxyethyl isocyanate, 2-methacryloyloxyethyl isocyanate, or 1,1-bis(acryloyloxymethyl)ethyl isocyanate; or a glycidyl group-containing (meth)acrylate monomer such as glycidyl (meth)acrylate or 4-hydroxybutyl acrylate glycidyl ether. (Meta)acrylate monomers having these reactive functional groups can be used alone or in combination of two or more.
[0096] The above acrylic resin intermediate is preferably copolymerized with a (meth)acrylate monomer having a glass transition temperature (Tg) of 50°C or higher, in that it has better adhesion to the substrate and forms a cured product with better processability, scratch resistance, and chemical resistance. Examples of such monomers include methyl (meth)acrylate, tert-butyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, isobornyl (meth)acrylate, dicyclofentanyl (meth)acrylate, adamanthyl (meth)acrylate, etc. It is preferable to use at least one of these monomers, and moreover, it is more preferable to use two or more in combination, and it is preferable that at least one of them is methyl (meth)acrylate, in order to obtain an acrylate (meth)acrylate resin capable of forming a cured product having excellent adhesion to the substrate, processability, scratch resistance, and chemical resistance. In addition, the values for the glass transition temperatures of the homopolymers of each component may be adopted from the values listed in Nikkan Kogyo Shinbunsha’s “Adhesion Technology Handbook,” Wiley-Interscience’s “Polymer Handbook,” Introduction to Resins for Paints, Kyoei Co., Ltd. HP, Mitsubishi Chemical Co., Ltd. HP, etc.
[0097] In addition, other polymerizable unsaturated group-containing compounds may be copolymerized with the above acrylic resin intermediate as needed. Examples of other polymerizable unsaturated group-containing compounds include, for instance, alkyl esters of (meth)acrylates such as ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate; (meth)acrylates containing a cyclo-ring such as isoboronyl (meth)acrylate and dicyclofentanyl (meth)acrylate; (meth)acrylates containing an aromatic ring such as phenyl (meth)acrylate and phenoxyethyl acrylate; (meth)acrylates containing a silyl group such as 3-methacryloxypropyltrimethoxysilane; and styrene derivatives such as styrene, α-methylstyrene, and chlorostyrene. Examples include (meth)acryloylmorpholine, diethylene glycol di(meth)acrylate, etc. These other polymerizable unsaturated group-containing compounds may be used alone or in combination of two or more.
[0098] When the above acrylic resin intermediate is obtained by copolymerizing the above (meth)acrylate monomer (α) and the above other polymerizable unsaturated group-containing compound, the reaction ratio of the two is such that the acrylic (meth)acrylate resin has excellent adhesion to the substrate and excellent processability, scratch resistance, and chemical resistance. Therefore, among the total of the two, the above (meth)acrylate monomer (α) is preferably 5 to 95 mass%, and more preferably 25 to 65%.
[0099] The above acrylic resin intermediate can be manufactured by a method similar to that used for general acrylic resins. For example, it can be manufactured by polymerizing various monomers in a temperature range of 60 to 150°C in the presence of a polymerization initiator. Examples of polymerization methods include bulk polymerization, solution polymerization, suspension polymerization, and emulsion polymerization. Additionally, examples of polymerization modes include random copolymers, block copolymers, and graft copolymers. When performing solution polymerization, ketone solvents such as methyl ethyl ketone or methyl isobutyl ketone, or glycol ether solvents such as propylene glycol monomethyl ether, propylene glycol dimethyl ether, propylene glycol monopropyl ether, or propylene glycol monobutyl ether may be preferably used.
[0100] The above (meth)acrylate monomer (β) is not particularly limited as long as it can react with the reactive functional group of the above (meth)acrylate monomer (α), but from the perspective of reactivity, it is preferable to have the following combination. That is, when the above hydroxyl group-containing (meth)acrylate is used as the above (meth)acrylate monomer (α), it is preferable to use the above isocyanate group-containing (meth)acrylate as the above (meth)acrylate monomer (β). When the above carboxyl group-containing (meth)acrylate is used as the above (meth)acrylate monomer (α), it is preferable to use the above glycidyl group-containing (meth)acrylate as the above (meth)acrylate monomer (β). When the isocyanate group-containing (meth)acrylate is used as the (meth)acrylate monomer (α), it is preferable to use the hydroxyl group-containing (meth)acrylate as the (meth)acrylate monomer (β). When the glycidyl group-containing (meth)acrylate is used as the (meth)acrylate monomer (α), it is preferable to use the carboxyl group-containing (meth)acrylate as the (meth)acrylate monomer (β).
[0101] The reaction between the acrylic resin intermediate and the (meth)acrylate monomer (β) can be carried out, for example, in the case where the reaction is an esterification reaction, by using an appropriate esterification catalyst such as triphenylphosphine at a temperature range of 60 to 150°C. In addition, in the case where the reaction is a urethane reaction, by reacting the (meth)acrylate monomer (β) dropwise with the acrylic resin intermediate at a temperature range of 50 to 120°C. The reaction ratio of the two is preferably in the range of 0.95 to 1.1 moles of the (meth)acrylate monomer (β) per 1 mole of the number of functional groups in the acrylic resin intermediate.
[0102] Among these, in order to have excellent adhesion to the substrate and to have better processability, scratch resistance, and chemical resistance, it is preferable that the acrylic (meth)acrylate resin (B) be a polymer of a monomer mixture composed of (meth)acrylate monomers, wherein the glycidyl group-containing (meth)acrylate monomer (x1) is contained in an amount of 5 to 60 parts by mass of the monomer mixture in 100 parts by mass of the monomer mixture. In particular, it is more preferable that the glycidyl group-containing (meth)acrylate monomer (x1) is used in an amount of 3 to 60 parts by mass, and in an amount of 5 to 40 parts by mass, by reacting a hydroxyl group-containing (meth)acrylate monomer (x2) and / or a carboxyl group-containing (meth)acrylate monomer (x3) with an acrylic polymer (b1) having the glycidyl group-containing (meth)acrylate monomer (x1) as an essential raw material. It is more desirable that it be.
[0103] In addition, it is preferable that the acrylic polymer (b1) is a copolymer of a glycidyl group-containing (meth)acrylate monomer (x1) and an (meth)acrylate alkyl ester, and it is even more preferable that the (meth)acrylate alkyl ester is a (meth)acrylate methyl ester.
[0104] The (meth)acryloyl group equivalent of the above acrylic (meth)acrylate resin (B) is preferably 300 to 3,000 g / equivalent in order to further improve the balance of durability and processability, such as weather resistance, and is particularly preferably 400 to 2,000 g / equivalent. In addition, the (meth)acryloyl group equivalent of the acrylic (meth)acrylate resin (B) in the present invention is a value calculated as a theoretical value from the reaction raw materials.
[0105] In addition, the weight average molecular weight (Mw) of the above acrylic (meth)acrylate resin (B) is 10,000 to 70,000, but 20,000 to 40,000 is more preferable in that it has excellent adhesion to the substrate and the balance of processability, scratch resistance, and chemical resistance is further improved.
[0106] In addition, in the present invention, the weight average molecular weight (Mw), number average molecular weight (Mn), and molecular weight distribution (Mn / Mw) are values measured by gel permeation chromatography (GPC).
[0107] The mass ratio (A / B) of the composite resin (A) and the (meth)acrylate resin (B) is preferably 2 / 98 to 90 / 10, more preferably 5 / 95 to 65 / 35, and more preferably 10 / 90 to 50 / 50, in order to obtain a coating film with excellent durability such as weather resistance and processability.
[0108] The active energy beam curable resin composition of the present invention contains the composite resin (A) and the acrylate (meth)acrylate resin (B), and may contain other active energy beam curable components, but in terms of excellent substrate adhesion, processability, scratch resistance, and chemical resistance, it is preferable that the content of the active energy beam curable component having a weight average molecular weight of 5,000 or less is 30 mass% or less of the total mass of the active energy beam curable components.
[0109] Other active energy beam curable components may include other (meth)acrylate compounds other than the acrylic (meth)acrylate resin (B). Examples of other (meth)acrylate compounds include dendrimer-type (meth)acrylate resins, urethane (meth)acrylate resins, epoxy (meth)acrylate resins, mono(meth)acrylate compounds and their modified forms, aliphatic hydrocarbon-type poly(meth)acrylate compounds and their modified forms, alicyclic poly(meth)acrylate compounds and their modified forms, aromatic poly(meth)acrylate compounds and their modified forms, etc. Each of these may be used individually or two or more types may be used in combination.
[0110] The content of the polysiloxane segment (a1) in the total resin component including the composite resin (A) and the acrylic (meth)acrylate resin (B) is preferably 2 to 55 mass% and more preferably 4 to 40 mass% in order to further improve the balance of durability and processability, such as weather resistance.
[0111] As the above photopolymerization initiator (C), for example, 1-hydroxycyclohexylphenyl ketone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, 1-[4-(2-hydroxyethoxy)phenyl]-2-hydroxy-2-methyl-1-propan-1-one, thioxanthone and thioxanthone derivatives, 2,2'-dimethoxy-1,2-diphenylethane-1-one, diphenyl(2,4,6-trimethoxybenzoyl)phosphine oxide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one, Examples of photoradical polymerization initiators include 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-1-butanone.
[0112] Commercially available products of the photopolymerization initiator (C) include, for example, “Omnirad 1173,” “Omnirad 184,” “Omnirad 127,” “Omnirad 2959,” “Omnirad 369,” “Omnirad 379,” “Omnirad 907,” and “Omnirad.” 4265”, “Omnirad 1000”, “Omnirad 651”, “Omnirad TPO”, “Omnirad 819”, “Omnirad 2022”, “Omnirad 2100”, “Omnirad 754”, “Omnirad 784”, “Omnirad 500”, “Omnirad 81” (manufactured by IGM Resins); Examples include “KAYACURE DETX”, “KAYACURE MBP”, “KAYACURE DMBI”, “KAYACURE EPA”, “KAYACURE OA” (manufactured by Nihon Kayaku Co., Ltd.); “Vicure 10”, “Vicure 55” (manufactured by Stoffa Chemical); “Trigonal P1” (manufactured by Akzo Nobel), “SANDORAY 1000” (manufactured by SANDOZ); “DEAP” (manufactured by Upjohn Chemical), “Quantacure PDO”, “Quantacure ITX”, “Quantacure EPD” (manufactured by Ward Blenkinsop); “Runtecure 1104” (manufactured by Runtec). These photopolymerization initiators may be used alone or in combination of two or more types.
[0113] The amount of the photopolymerization initiator (C) added is preferably in the range of 0.05 to 15 mass% of the total components other than the solvent of the active energy beam curable resin composition, for example, and more preferably in the range of 0.1 to 10 mass%.
[0114] In addition, the above photopolymerization initiator may be used in combination with photosensitizers such as amine compounds, urea compounds, sulfur compounds, phosphorus compounds, chlorine compounds, and nitrile compounds, as needed.
[0115] In addition, the active energy beam curable resin composition of the present invention may contain other components other than those described above. Examples of such other components include inorganic fine particles, silane coupling agents, phosphate ester compounds, solvents, ultraviolet absorbers, antioxidants, silicone-based additives, fluorine-based additives, antistatic agents, organic beads, quantum dots (QDs), rheology control agents, defoaming agents, anti-fogging agents, coloring agents, etc.
[0116] The above-mentioned inorganic fine particles are added for purposes such as adjusting the hardness or refractive index of the cured film of an active energy beam curable resin composition, and various known and commonly used inorganic fine particles may be used. Examples include fine particles such as silica, alumina, zirconia, titania, barium titanate, and antimony trioxide. Each of these may be used individually, or two or more types may be used in combination.
[0117] Among these inorganic fine particles, silica particles are preferred because they are easy to obtain and easy to handle. Examples of silica particles include fumed silica, precipitated silica, gel silica, sol-gel silica, and other wet silica, and any of them may be used.
[0118] The above-mentioned inorganic fine particles may have functional groups introduced to the surface of the fine particles using various silane coupling agents. By introducing functional groups to the surface of the said inorganic fine particles, the miscibility with organic components such as the above-mentioned acrylate (meth)acrylate resin (B) is increased, thereby improving storage stability.
[0119] The silane coupling agent modifying the above-mentioned inorganic fine particles is, for example, a (meth)acryloyloxy-based silane coupling agent such as [(meth)acryloyloxyalkyl]trialkylsilane, [(meth)acryloyloxyalkyl]dialkylalkoxysilane, [(meth)acryloyloxyalkyl]alkyldialkylkoxysilane, [(meth)acryloyloxyalkyl]trialkoxysilane, etc.; a vinyl-based silane coupling agent such as trialkylvinylsilane, dialkylalkoxyvinylsilane, alkyldialkylkoxyvinylsilane, trialkoxyvinylsilane, trialkylallylsilane, dialkylalkoxyallylsilane, alkyldialkylkoxyallylsilane, trialkoxyallylsilane, etc.; and a styrene-based silane coupling agent such as styryltrialkyl, styryldialkylalkoxysilane, styrylalkyldialkylkoxysilane, styryltrialkoxysilane, etc. Epoxy-based silane coupling agents such as (glycidyloxyalkyl)trialkylsilane, (glycidyloxyalkyl)dialkylalkoxysilane, (glycidyloxyalkyl)alkyldialkylkoxysilane, (glycidyloxyalkyl)trialkoxysilane, [(3,4-epoxycyclohexyl)alkyl]trimethoxysilane, [(3,4-epoxycyclohexyl)alkyl]trialkylsilane, [(3,4-epoxycyclohexyl)alkyl]dialkylalkoxysilane, [(3,4-epoxycyclohexyl)alkyl]alkyldialkylkoxysilane, [(3,4-epoxycyclohexyl)alkyl]trialkoxysilane, etc. Examples of isocyanate-based silane coupling agents include (isocyanate alkyl)trialkylsilane, (isocyanate alkyl)dialkylalkoxysilane, (isocyanate alkyl)alkyldialkoxysilane, (isocyanate alkyl)trialkoxysilane, etc. These may be used individually or in combination of two or more types.
[0120] Among the above silane coupling agents, (meth)acryloyloxy-based silane coupling agents are preferred in that they become inorganic fine particles with excellent miscibility with organic components such as the above acrylate (meth)acrylate resin, and [(meth)acryloyloxyalkyl]trialkoxysilanes such as 3-(meth)acryloyloxypropyltrimethoxysilane are particularly preferred.
[0121] The average particle size of the above-mentioned inorganic fine particles is not particularly limited and may be adjusted appropriately depending on the desired performance of the cured material. In particular, in order to obtain a cured film with excellent anti-blocking properties and transparency in addition to scratch resistance and crack prevention properties, the average particle size of the above-mentioned inorganic fine particles is preferably in the range of 80 to 250 nm, more preferably in the range of 90 to 180 nm, and particularly preferably in the range of 100 to 150 nm.
[0122] In addition, the average particle size of the above-mentioned inorganic fine particles is a value obtained by measuring the particle size in the active energy beam curable resin composition under the following conditions.
[0123] Particle diameter measuring device: "ELSZ-2" manufactured by Otsuka Denshi Co., Ltd.
[0124] Particle size measurement sample: Active energy beam curable resin composition prepared as a methyl isobutyl ketone solution with a non-volatile content of 1 mass%.
[0125] In the active energy beam curable resin composition of the present invention, the content of the inorganic fine particles is not particularly limited and may be appropriately adjusted according to the desired cured product performance, etc. In particular, in order to obtain a cured film with excellent scratch resistance, the content of the inorganic fine particles is preferably in the range of 10 to 100 parts by mass with respect to 100 parts by mass of the acrylate (meth)acrylate resin.
[0126] The silane coupling agent added to the above active energy beam curable resin composition is, for example, a (meth)acryloyloxy-based silane coupling agent such as [(meth)acryloyloxyalkyl]trialkylsilane, [(meth)acryloyloxyalkyl]dialkylalkoxysilane, [(meth)acryloyloxyalkyl]alkyldialkylkoxysilane, [(meth)acryloyloxyalkyl]trialkoxysilane; a vinyl-based silane coupling agent such as trialkylvinylsilane, dialkylalkoxyvinylsilane, alkyldialkylkoxyvinylsilane, trialkoxyvinylsilane, trialkylallylsilane, dialkylalkoxyallylsilane, alkyldialkylkoxyallylsilane, trialkoxyallylsilane; and a styrene-based silane coupling agent such as styryltrialkyl, styryldialkylalkoxysilane, styrylalkyldialkylkoxysilane, styryltrialkoxysilane. Epoxy-based silane coupling agents such as (glycidyloxyalkyl)trialkylsilane, (glycidyloxyalkyl)dialkylalkoxysilane, (glycidyloxyalkyl)alkyldialkylkoxysilane, (glycidyloxyalkyl)trialkoxysilane, [(3,4-epoxycyclohexyl)alkyl]trimethoxysilane, [(3,4-epoxycyclohexyl)alkyl]trialkylsilane, [(3,4-epoxycyclohexyl)alkyl]dialkylalkoxysilane, [(3,4-epoxycyclohexyl)alkyl]alkyldialkylkoxysilane, [(3,4-epoxycyclohexyl)alkyl]trialkoxysilane, etc. Examples of isocyanate-based silane coupling agents include (isocyanate alkyl)trialkylsilane, (isocyanate alkyl)dialkylalkoxysilane, (isocyanate alkyl)alkyldialkoxysilane, (isocyanate alkyl)trialkoxysilane, etc. These may be used individually or in combination of two or more types.
[0127] As commercially available products of the above phosphate ester compounds, for example, phosphate ester compounds having (meth)acryloyl groups in their molecular structure, such as "Kayama PM-2" and "Kayama PM-21" manufactured by Nihon Kayaku Co., Ltd., "Light Ester P-1M", "Light Ester P-2M" and "Light Acrylate P-1A(N)" manufactured by Kyoei Co., Ltd., "SIPOMER PAM 100", "SIPOMER PAM 200", "SIPOMER PAM 300" and "SIPOMER PAM 4000" manufactured by SOLVAY, "Viscot #3 PA" and "Viscot #3 PMA" manufactured by Osaka Yugi Kigaku Kogyo, and "New Frontier S-23A" manufactured by Daiichi Gokyosei Yakusha; Examples include SOLVAY’s “SIPOMER PAM 5000,” a phosphate ester compound having an allyl ether group in its molecular structure.
[0128] The above solvent is added for purposes such as controlling the coating viscosity of the active energy beam curable resin composition, and its type and amount are appropriately adjusted according to the desired performance. Generally, it is used so that the non-volatile content of the active energy beam curable resin composition is in the range of 10 to 90 mass%. Specific examples of the above solvent include, for instance, ketone solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone; cyclic ether solvents such as tetrahydrofuran, dioxolane; esters such as methyl acetate, ethyl acetate, butyl acetate; aromatic solvents such as toluene, xylene; alicyclic solvents such as cyclohexane, methylcyclohexane; and alcohol solvents such as carbitol, cellosolve, methanol, isopropanol, butanol, propylene glycol monomethyl ether. Examples include glycol ether-based solvents such as ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, and propylene glycol monopropyl ether. These solvents may be used alone or in combination of two or more types.
[0129] Examples of the above-mentioned ultraviolet absorbers include triazine derivatives such as 2-[4-{(2-hydroxy-3-dodecyloxypropyl)oxy}-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, 2-[4-{(2-hydroxy-3-tridecyloxypropyl)oxy}-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, 2-(2'-xanthencarboxy-5'-methylphenyl)benzotriazole, 2-(2'-o-nitrobenzyloxy-5'-methylphenyl)benzotriazole, 2-xanthencarboxy-4-dodecyloxybenzophenone, 2-o-nitrobenzyloxy-4-dodecyloxybenzophenone, etc. These ultraviolet absorbers can be used alone or in combination of two or more types.
[0130] Examples of the above antioxidants include hindered phenol-based antioxidants, hindered amine-based antioxidants, organic sulfur-based antioxidants, phosphate ester-based antioxidants, etc. These antioxidants may be used alone or in combination of two or more types.
[0131] Examples of the above silicone-based additives include polyorganosiloxanes having alkyl or phenyl groups, such as dimethylpolysiloxane, methylphenylpolysiloxane, cyclic dimethylpolysiloxane, methylhydrogenpolysiloxane, polyether-modified dimethylpolysiloxane copolymer, polyester-modified dimethylpolysiloxane copolymer, fluorine-modified dimethylpolysiloxane copolymer, amino-modified dimethylpolysiloxane copolymer, polyether-modified polydimethylsiloxane having acrylic groups, and polyester-modified polydimethylsiloxane having acrylic groups. These silicone-based additives may be used alone or in combination of two or more types.
[0132] Examples of commercially available fluorine-based additives include the "Megaface" series manufactured by DIC Co., Ltd. These fluorine-based additives may be used alone or in combination of two or more types.
[0133] Examples of the above antistatic agents include pyridinium, imidazolium, phosphonium, ammonium, or lithium salts of bis(trifluoromethanesulfonyl)imide or bis(fluorosulfonyl)imide. These antistatic agents may be used alone or in combination of two or more types.
[0134] Examples of the above organic beads include polymethyl methacrylate beads, polycarbonate beads, polystyrene beads, polyacrylstyrene beads, silicone beads, glass beads, acrylic beads, benzoguanamine-based resin beads, melamine-based resin beads, polyolefin-based resin beads, polyester-based resin beads, polyamide-based resin beads, polyimide-based resin beads, polyfluoroethylene resin beads, polyethylene resin beads, etc. These organic beads may be used individually or in combination of two or more types. In addition, the average particle size of these organic beads is preferably in the range of 1 to 10 μm.
[0135] Examples of the above quantum dots (QDs) include II-V semiconductor compounds, II-VI semiconductor compounds, III-IV semiconductor compounds, III-V semiconductor compounds, III-VI semiconductor compounds, IV-VI semiconductor compounds, I-III-VI semiconductor compounds, II-IV-VI semiconductor compounds, II-IV-V semiconductor compounds, I-II-IV-VI semiconductor compounds, Group IV elements, or compounds containing the same. The above II-VI semiconductor compounds include, for example, binary compounds such as ZnO, ZnS, ZnSe, ZnTe, CdS, CdSe, CdTe, HgS, HgSe, and HgTe; Examples include ternary compounds such as ZnSeS, ZnSeTe, ZnSTe, CdZnS, CdZnSe, CdZnTe, CdSeS, CdSeTe, CdSTe, CdHgS, CdHgSe, CdHgTe, HgSeS, HgSeTe, HgSTe, HgZnS, HgZnSe, and HgZnTe; and quaternary compounds such as CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, CdHgZnTe, HgZnSeS, HgZnSeTe, and HgZnSTe. Examples of the above group III-IV semiconductor compounds include B4C3, Al4C3, Ga4C3, etc.The above III-V semiconductor compounds may include, for example, binary compounds such as BP, BN, AlN, AlP, AlAs, AlSb, GaN, GaP, GaAs, GaSb, InN, InP, InAs, and InSb; ternary compounds such as GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, and GaAlNP; and quaternary compounds such as GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs, and InAlPSb. Examples of the above III-VI group semiconductor compounds include Al2S3, Al2Se3, Al2Te3, Ga2S3, Ga2Se3, Ga2Te3, GaTe, In2S3, In2Se3, In2Te3, InTe, etc. Examples of the above IV-VI group semiconductor compounds include binary compounds such as SnS, SnSe, SnTe, PbS, PbSe, and PbTe; ternary compounds such as SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, and SnPbTe; and quaternary compounds such as SnPbSSe, SnPbSeTe, and SnPbSTe. Examples of the above Group I-III-VI semiconductor compounds include CuInS2, CuInSe2, CuInTe2, CuGaS2, CuGaSe2, CuGaSe2, AgInS2, AgInSe2, AgInTe2, AgGaSe2, AgGaS2, AgGaTe2, etc. Examples of the above Group IV elements or compounds containing them include C, Si, Ge, SiC, SiGe, etc. The quantum dot may be composed of a single semiconductor compound or may have a core-shell structure composed of multiple semiconductor compounds.In addition, the surface may be modified with an organic compound.
[0136] These various additives can be added in any amount depending on the desired performance, but generally, it is preferable to use them in the range of 0.01 to 40 mass% of the total 100 mass% of the components excluding the solvent in the active energy beam curable resin composition.
[0137] The active energy beam curable resin composition used in the present invention is prepared by mixing each of the above-mentioned formulation components. The mixing method is not particularly limited, and a paint shaker, disperser, roll mill, bead mill, ball mill, atlighter, sand mill, bead mill, etc. may be used.
[0138] The cured film of the present invention can be obtained by irradiating the active energy beam curable resin composition with an active energy beam. Examples of the active energy beams include ionizing radiation such as ultraviolet rays, electron beams, alpha rays, beta rays, and gamma rays. Furthermore, when using ultraviolet rays as the active energy beams, irradiation may be performed under an inert gas atmosphere such as nitrogen gas or under an air atmosphere to efficiently carry out the curing reaction by ultraviolet rays.
[0139] As sources of ultraviolet radiation, UV lamps are generally used due to their practicality and economic efficiency. Specifically, examples include low-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, xenon lamps, gallium lamps, metal halide lamps, sunlight, and LEDs.
[0140] The accumulated light intensity of the above active energy line is not particularly limited, but is preferably 0.1 to 50 kJ / m², and more preferably 0.5 to 10 kJ / m². An accumulated light intensity within the above range is desirable in that it can prevent or suppress the occurrence of uncured parts.
[0141] In addition, the irradiation of the above active energy rays may be performed in a single stage or divided into two or more stages.
[0142] In addition, tanδ, measured by the dynamic viscoelastic spectrum of the cured film, is preferably in the range of 0.1 to 1, as it has excellent adhesion and excellent processability, scratch resistance, and chemical resistance.
[0143] The articles of the present invention have the above-mentioned cured film on their surface. Examples of the above articles include plastic molded articles such as interior and exterior materials in the construction field, mobile phones, home appliances, interior and exterior materials for automobiles, and OA equipment.
[0144] [Example]
[0145] The present invention will be specifically explained below through examples and comparative examples. Furthermore, the present invention is not limited to the examples exemplified below.
[0146] Also, in this embodiment, the weight average molecular weight (Mw) is a value measured under the following conditions using gel permeation chromatography (GPC).
[0147] Measuring device; "HLC-8220" manufactured by Dosō Kabushiki Kaisha
[0148] Column; Produced by Doso Kabushiki Kaisha "Guard Column H" XL -H」
[0149] +Toso Kabushiki Kaisha "TSKgel G5000HXL"
[0150] +Toso Kabushiki Kaisha "TSKgel G4000HXL"
[0151] +Toso Kabushiki Kaisha "TSKgel G3000HXL"
[0152] +Toso Kabushiki Kaisha "TSKgel G2000HXL"
[0153] Detector; RI (Refractor)
[0154] Data processing: Doso Kabushiki Kaisha "SC-8010"
[0155] Measurement conditions: Column temperature 40℃
[0156] Solvent tetrahydrofuran
[0157] Flow rate 1.0 ml / min
[0158] Standard; Polystyrene
[0159] Sample; 100 μl of a tetrahydrofuran solution with a resin solid content of 0.4 mass% filtered through a microfilter
[0160] (Synthetic Example 1: Synthesis of Composite Resin (A-1))
[0161] 244 parts by mass of butanol and 44 parts by mass of phenyltrimethoxysilane (PTMS) were added to a reaction vessel equipped with a stirrer, a thermometer, a dropping funnel, a cooling tube, and a nitrogen gas inlet, and the temperature was raised to 100°C. Subsequently, a mixture consisting of 153 parts by mass of methyl methacrylate (MMA), 30 parts by mass of tertiary butyl methacrylate (t-BMA), 42 parts by mass of butyl acrylate (BA), 6 parts by mass of acrylic acid (AA), 60 parts by mass of cyclohexyl methacrylate (CHMA), 9 parts by mass of 3-methacryloyloxypropyltrimethoxysilane (MPTS), and 12 parts by mass of tert-butylperoxy-2-ethylhexanoate (TBPEH) was dropped into the reaction vessel at the same temperature while stirring under the passage of nitrogen gas over a period of 5 hours. After that, 600 parts by mass of a vinyl polymer (a2-1) having trimethoxysilyl groups was prepared by stirring at the same temperature for 5 hours.
[0162] Next, the temperature of the reaction vessel was adjusted to 80°C, and 64 parts by mass of methyltrimethoxysilane (MTMS), 269 parts by mass of 3-methacryloyloxypropyltrimethoxysilane (MPTS), and 53 parts by mass of dimethyldimethoxysilane (DMDMS) were added to the reaction vessel. Then, a mixture of 0.8 parts by mass of “A-3” [iso-propyl acid phosphate manufactured by Sakai Chemical Co., Ltd.] and 120 parts by mass of deionized water was added dropwise over 5 minutes, and a hydrolysis condensation reaction was carried out by stirring at the same temperature for 4 hours to obtain a reaction product. When the reaction product was analyzed by 1H-NMR, nearly 100% of the trimethoxysilyl groups of the vinyl polymer (a2-1) were hydrolyzed. After that, the reaction product was distilled for 2 hours under reduced pressure of 10 to 300 kPa and conditions of 40 to 60°C to remove the generated methanol and water, and then 200 parts by mass of n-butyl acetate and 55 parts by mass of methyl ethyl ketone (MEK) were added to obtain 1,000 parts by mass of a solution of a composite resin (A1) consisting of a polysiloxane segment (a1) and a vinyl polymer segment (a2) having a non-volatile content of 60.1%. The polysiloxane segment (a1) in this composite resin (A-1) was 50% by mass.
[0163] (Synthetic Example 2: Synthesis of Composite Resin (A-2))
[0164] 56 parts by mass of n-butyl acetate and 13 parts by mass of PTMS were added to a reaction vessel similar to Synthesis Example 1, and the temperature was raised to 100°C. Subsequently, a mixture consisting of 128 parts by mass of MMA, 204 parts by mass of BA, 15 parts by mass of methacrylic acid (MA), 51 parts by mass of ethyl acrylate (EA), 77 parts by mass of styrene (St), 36 parts by mass of MPTS, and 20 parts by mass of TBPEH was dropped into the reaction vessel over a period of 5 hours while stirring under the same temperature and nitrogen gas aeration. Afterward, 600 parts by mass of a vinyl polymer (a2-2) having trimethoxysilyl groups was prepared by stirring at the same temperature for 7 hours.
[0165] Next, the temperature of the reaction vessel was adjusted to 90°C, and 18 parts by mass of MTMS, 83 parts by mass of MPTS, and 15 parts by mass of DMDMS were added to the reaction vessel. Then, a mixture of 0.2 parts by mass of “A-3” [iso-propyl acid phosphate manufactured by Sakai Chemical Co., Ltd.] and 40 parts by mass of deionized water was added dropwise over 5 minutes, and a hydrolysis condensation reaction was carried out by stirring at the same temperature for 2 hours to obtain a reaction product. When the reaction product was analyzed by 1H-NMR, nearly 100% of the trimethoxysilyl groups of the vinyl polymer (a2-2) were hydrolyzed. After that, the reaction product was distilled for 2 hours under reduced pressure of 10 to 300 kPa and conditions of 40 to 60°C to remove the generated methanol and water, and then 250 g of n-butyl acetate and 130 g of methyl ethyl ketone (MEK) were added to obtain 1,000 parts by mass of a composite resin (A2) consisting of a polysiloxane segment (a1) and a vinyl polymer segment (a2) having a non-volatile content of 60.2%. The polysiloxane segment (a1) in the composite resin (A-2) was 15% by mass.
[0166] (Synthetic Example 3: Synthesis of Composite Resin (A-3))
[0167] 128 parts by mass of n-butyl acetate and 36 parts by mass of PTMS were added to a reaction vessel similar to Synthesis Example 1, and the temperature was raised to 120°C. Subsequently, a mixture consisting of 118 parts by mass of MMA, 126 parts by mass of t-BMA, 105 parts by mass of BA, 42 parts by mass of EA, 8.4 parts by mass of AA, 21 parts by mass of MPTS, and 16 parts by mass of TBPEH was dropped into the reaction vessel over a period of 5 hours while stirring under the same temperature and nitrogen gas aeration. Afterward, 600 parts by mass of a vinyl polymer (a2-3) having trimethoxysilyl groups was prepared by stirring at the same temperature for 7 hours.
[0168] Next, the temperature of the reaction vessel was adjusted to 95°C, and 8.7 parts by mass of MTMS, 192 parts by mass of MPTS, and 11 parts by mass of DMDMS were added to the reaction vessel. Then, a mixture of 0.8 parts by mass of “A-3” [iso-propyl acid phosphate manufactured by Sakai Chemical Co., Ltd.] and 100 parts by mass of deionized water was added dropwise over 5 minutes, and a hydrolytic condensation reaction was carried out by stirring at the same temperature for 5 hours to obtain a reaction product. When the reaction product was analyzed by 1H-NMR, nearly 100% of the trimethoxysilyl groups of the vinyl polymer (a2-3) were hydrolyzed. After that, the reaction product was distilled for 2 hours under reduced pressure of 10 to 300 kPa and conditions of 40 to 60°C to remove the generated methanol and water, and then 250 g of n-butyl acetate and 120 g of butanol (n-BuOH) were added to obtain 1000 parts by mass of a composite resin (A3) consisting of a polysiloxane segment (a1) and a vinyl polymer segment (a2) having a non-volatile content of 60.0%. The polysiloxane segment (a1) in this composite resin (A-3) was 30% by mass.
[0169] (Synthetic Example 4: Synthesis of Composite Resin (A-4))
[0170] 313 parts by mass of n-butyl acetate and 121 parts by mass of PTMS were added to a reaction vessel similar to Synthesis Example 1, and the temperature was raised to 120°C. Subsequently, a mixture consisting of 77 parts by mass of MMA, 15 parts by mass of t-BMA, 21 parts by mass of BA, 3 parts by mass of AA, 30 parts of CHMA, 4.5 parts by mass of MPTS, and 16 parts by mass of TBPEH was dropped into the reaction vessel over a period of 5 hours while stirring under the same temperature and nitrogen gas aeration. Afterward, 600 parts by mass of a vinyl polymer (a2-4) having trimethoxysilyl groups was prepared by stirring at the same temperature for 7 hours.
[0171] Next, the temperature of the reaction vessel was adjusted to 95°C, and 117 parts by mass of MTMS, 339 parts by mass of MPTS, and 73 parts by mass of DMDMS were added to the reaction vessel. Then, a mixture of 2.3 parts by mass of “A-3” [iso-propyl acid phosphate manufactured by Sakai Chemical Co., Ltd.] and 100 parts by mass of deionized water was added dropwise over 5 minutes, and a hydrolysis condensation reaction was carried out by stirring at the same temperature for 5 hours to obtain a reaction product. When the reaction product was analyzed by 1H-NMR, nearly 100% of the trimethoxysilyl groups of the vinyl polymer (a2-4) were hydrolyzed. After that, the reaction product was distilled for 4 hours under reduced pressure of 10 to 300 kPa and conditions of 40 to 60°C to remove the generated methanol and water, and then 70 g of n-BuOH was added to obtain 1000 parts by mass of a composite resin (A4) consisting of a polysiloxane segment (a1) and a vinyl polymer segment (a2) having a non-volatile content of 60.0%. The polysiloxane segment (a1) in this composite resin (A-4) was 75% by mass.
[0172] (Synthetic Example 5: Synthesis of Composite Resin (A-5))
[0173] 149 parts by mass of n-butyl acetate and 113 parts by mass of PTMS were added to a reaction vessel similar to Synthesis Example 1, and the temperature was raised to 110°C. Subsequently, a mixture consisting of 15 parts by mass of MMA, 3 parts by mass of t-BMA, 4 parts by mass of BA, 0.6 parts by mass of AA, 6 parts of CHMA, 0.9 parts by mass of MPTS, and 8 parts by mass of TBPEH was dropped into the reaction vessel over a period of 5 hours while stirring under the same temperature and nitrogen gas aeration. Afterward, 300 parts by mass of a vinyl polymer (a2-5) having trimethoxysilyl groups was prepared by stirring at the same temperature for 7 hours.
[0174] Next, the temperature of the reaction vessel was adjusted to 95°C, and 103 parts by mass of MTMS, 478 parts by mass of MPTS, and 129 parts by mass of DMDMS were added to the reaction vessel. Then, a mixture of 1.5 parts by mass of “A-3” [iso-propyl acid phosphate manufactured by Sakai Chemical Co., Ltd.] and 185 parts by mass of deionized water was added dropwise over 5 minutes, and a hydrolysis condensation reaction was carried out by stirring at the same temperature for 5 hours to obtain a reaction product. When the reaction product was analyzed by 1H-NMR, nearly 100% of the trimethoxysilyl groups of the vinyl polymer (a2-5) were hydrolyzed. After that, the reaction product was distilled for 5 hours under reduced pressure of 10 to 300 kPa and conditions of 40 to 60°C to remove the generated methanol and water, and then 104 parts by mass of n-butyl acetate and 200 g of n-BuOH were added to obtain 1000 parts by mass of a composite resin (A5) consisting of a polysiloxane segment (a1) and a vinyl polymer segment (a2) having a non-volatile content of 60.3%. The polysiloxane segment (a1) in this composite resin (A-5) was 95% by mass.
[0175] (Synthesizing Example 6: Preparation of acrylic (meth)acrylate resin (B-1))
[0176] 387 parts by mass of methyl isobutyl ketone (MIBK) were added to a reaction vessel similar to Synthesis Example 1, and the temperature was raised to 110°C while stirring. Subsequently, a mixture consisting of 57 parts by mass of glycidyl methacrylate (GMA), 513 parts by mass of MMA, and 10 parts by mass of TBPEH was added dropwise from a dropping funnel over a period of 3 hours, and the temperature was maintained at 110°C for 15 hours. After cooling to 90°C, 0.3 parts by mass of methoquinone (MQ) and 29 parts by mass of AA were added, followed by the addition of 3.1 parts by mass of triphenylphosphine (TPP). The temperature was further raised to 100°C and maintained for 8 hours to obtain 1000 parts by mass of a solution of acrylate (meth)acrylate resin (B-1) having a non-volatile content of 59.9%. The weight average molecular weight (Mw) of this acrylic (meth)acrylate resin (B-1) was 24,300, and the theoretical value of the (meth)acryloyl group equivalent calculated from the input ratio of the raw materials was 1530 g / equivalent.
[0177] (Synthesized Examples 7–14: Preparation of acrylic (meth)acrylate resins (B-2)–(B-9))
[0178] Acrylates (B-2) to (B-9) were obtained by the same method as Synthesis Example 6, except that the mixing ratios shown in Tables 2 and 3 were changed.
[0179] (Synthesizing Example 15: Preparation of Acrylic (Meta)Acrylate Resin (RB-1))
[0180] Acrylate (meth)acrylate (RB-1) was obtained by the same method as Synthesis Example 6, except that the mixing ratio was changed to the one shown in Table 3.
[0181] The composition and properties of the acrylic (meth)acrylates (B-1) to (B-9) and (RB-1) obtained in Synthesis Examples 6 to 15 are shown in Tables 1 and 2.
[0182] [Table 1]
[0183]
[0184] The abbreviations in Table 1 are as follows.
[0185] MMA: Methyl methacrylate (Tg of homopolymer: 105℃)
[0186] GMA: Glycidyl methacrylate (Tg of homopolymer: 4℃)
[0187] AA: Acrylic acid (Tg of homopolymer: -15℃)
[0188] MIBK: Methyl isobutyl ketone
[0189] PO: t-butylperoxy-2-ethylhexanoate (Nihon Nyukazai Co., Ltd. "Perbutyl O")
[0190] MQ: Methoquinone (paramethoxyphenol)
[0191] TPP: Triphenylphosphine
[0192] [Table 2]
[0193]
[0194] The abbreviations in Table 2 are as follows.
[0195] t-BMA: Tertiary butyl methacrylate (Tg of homopolymer: 107℃)
[0196] CHMA: Cyclohexyl methacrylate (Tg of homopolymer: 66℃)
[0197] IBXMA: Isobornyl methacrylate (Tg of homopolymer: 180℃)
[0198] BZMA: Benzyl methacrylate (Tg of homopolymer: 54℃)
[0199] (Example 1: Preparation and evaluation of active energy beam curable resin composition (1))
[0200] 10 parts by mass of a solution of the composite resin (A-1) obtained in Synthesis Example 1 (6 parts by mass as the composite resin (A-1)), 157 parts by mass of a solution of the acrylic (meth)acrylate resin (B-1) obtained in Synthesis Example 6 (94 parts by mass as the acrylic (meth)acrylate resin (B-1)), and 2.4 parts by mass of a photopolymerization initiator ("Omnirad-184" manufactured by IGM Resins) were mixed to obtain an active energy beam curable resin composition (1).
[0201] [Method for preparing a cured film for evaluation]
[0202] The active energy beam curable resin composition obtained above was applied to a polycarbonate substrate such that the thickness of the cured film was 20 μm, dried for 2 minutes under an environment of 80°C, and then irradiated with 1000 mJ under a high-pressure mercury lamp of 80 W / cm² to obtain a cured film.
[0203] [Evaluation of Coating Appearance]
[0204] The cured coating film obtained above was observed by visual inspection, and the appearance of the coating film was evaluated according to the following criteria.
[0205] ○: No crack is detected.
[0206] △: The occurrence of a slight crack is confirmed.
[0207] ×: The occurrence of a crack is confirmed.
[0208] [Evaluation of Closeness]
[0209] The cured coating obtained above was measured according to the JIS K-5600 base test method. A 1mm wide cut was made on the cured coating with a cutter to make 100 bases, and cellophane tape was applied to cover all bases. The tape was then quickly pulled and peeled off, and the number of remaining bases was counted and evaluated according to the following criteria.
[0210] ○: No peeling.
[0211] △: The area of peeling is 1~64% of the total base timber area.
[0212] ×: The area of peeling is 65% or more of the total base timber area.
[0213] [Evaluation of Content]
[0214] The condition of the cured film obtained above after rubbing it back and forth 50 times with a felt impregnated with methyl ethyl ketone was determined by touch and visual inspection, and evaluated according to the following criteria.
[0215] ○: No softening or gloss reduction is observed.
[0216] △: Slight softening or a decrease in gloss is observed.
[0217] ×: Significant softening or a decrease in gloss is observed.
[0218] [Assessment of Scratch Resistance]
[0219] A disc-shaped indenter with a diameter of 2.4 centimeters was wrapped with 0.5 g of steel wool ("Bone Star #0000" manufactured by Nippon Steel Wool Co., Ltd.), and a load of 500 g was applied to the indenter. An abrasion test was performed by reciprocating the evaluation cured film obtained above 10 times. The haze values of the cured film before and after the abrasion test were measured using a "Turbidity Meter NDH5000" manufactured by Nippon Tenshoku Kogyo Co., Ltd., and the difference between them (dH) was used to evaluate according to the following criteria. Furthermore, the smaller the difference (dH), the higher the resistance to abrasion.
[0220] ○: dH is 1.0% or less.
[0221] △: dH is greater than 1.0% and less than or equal to 3.0%.
[0222] ×: dH is greater than 3.0%.
[0223] [Evaluation of Weather Resistance (Appearance)]
[0224] For the cured coating film obtained above, the coating film was observed by visual inspection after 1,000 hours of exposure using a DuPanel light weather meter (manufactured by Sugashi Kenki Co., Ltd., during light irradiation: 30W / ㎡, 70℃; during wet: humidity 90% or higher, 50℃, light irradiation / wetting cycle = 8 hours / 4 hours), and the appearance of the coating film was evaluated according to the following criteria.
[0225] ○: No crack is detected.
[0226] △: The occurrence of a slight crack is confirmed.
[0227] ×: The occurrence of a crack is confirmed.
[0228] [Evaluation of Weather Resistance (Gloss Retention Rate)]
[0229] The specular reflectance (gloss value) (%) of evaluation cured film A immediately after production and the specular reflectance (gloss value) (%) of the film after 1,000 hours of exposure to a QUV ultraviolet fluorescent lamp type accelerated weathering tester (manufactured by Q-Lab Corporation, control wavelength 310 nm, during light irradiation: 0.71 W / ㎡, 60℃; during wetting: humidity 90% or higher, 50℃, light irradiation / wetting cycle = 4 hours / 4 hours) were evaluated as the retention rate (gloss retention rate: %) relative to the specular reflectance (gloss value) of the cured film before exposure [(100 × specular reflectance of the film after exposure) / (specular reflectance of the cured film before exposure)]. A higher retention rate indicates better weather resistance. Specular reflectance was measured using Micro-Tri-Gloss manufactured by BYK Corporation.
[0230] [Evaluation of Stain Resistance]
[0231] The cured coating film obtained above was subjected to exposure for three months at the DIC Co., Ltd. Sakai Plant in Takaishi City, Osaka Prefecture. The color difference (ΔE) between the finely defined coating film after the exposure test and the coating film before the exposure test was evaluated using the "CM-3500d" manufactured by Konica Minolta Sensing Co., Ltd. A smaller color difference (ΔE) indicates better stain resistance.
[0232] [Evaluation of Processability]
[0233] As an evaluation of processability, film elongation was measured. The greater the film elongation, the better the processability.
[0234] (Method for measuring the degree of sin)
[0235] The active energy beam curable resin composition obtained above was applied to a polyethylene terephthalate (PET) film with a thickness of 125 μm using a bar coater and dried at 80°C for 1 minute. Subsequently, by irradiating ultraviolet rays with a high-pressure mercury lamp (1000 mJ / cm²) under an air atmosphere, a laminated film having a cured material with a film thickness of 5 μm laminated on the PET film was obtained.
[0236] A laminated film was cut into a test specimen with a width of 10 mm × a length of 100 mm, and a tensile test was performed on the obtained test specimen under the following conditions.
[0237] "Autograph AGS-1kNG" manufactured by Shimadzu Seisakusho Co., Ltd. (Tensile speed: 10 mm / min, Chuck distance: 40 mm, Measurement atmosphere: 25℃)
[0238] (Examples 2 to 15: Preparation of active energy beam curable resin compositions (2) to (15))
[0239] Except for changing the mixing ratios shown in Tables 3 to 5, active energy beam curable resin compositions (2) to (15) were obtained in the same manner as in Example 1, and each evaluation was performed.
[0240] (Comparative Examples 1-3: Preparation of acrylate resins (R1) to (R3))
[0241] Except for changing the mixing ratio shown in Table 6, active energy beam curable resin compositions (R1) to (R3) were obtained in the same manner as in Example 1, and each evaluation was performed.
[0242] The composition and evaluation results of the active energy beam curable resins (1) to (15) and (R1) to (R3) prepared in Examples 1 to 15 and Comparative Examples 1 to 3 are shown in Tables 3 to 6.
[0243] [Table 3]
[0244]
[0245] [Table 4]
[0246]
[0247] [Table 5]
[0248]
[0249] The abbreviations in Table 5 are as follows.
[0250] DPHA: A mixture of dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate
[0251] PETA: A mixture of pentaerythritol tetraacrylate and pentaerythritol triacrylate
[0252] Photopolymerization initiator: Omnirad 184 (IGM Resins "Omnirad 184")
[0253] [Table 6]
[0254]
[0255] It has been confirmed that the cured film obtained from Examples 1 to 15, which are active energy beam curable resin compositions of the present invention, has excellent film appearance, adhesion, solvent resistance, scratch resistance, weather resistance, stain resistance, and processability.
[0256] Meanwhile, Comparative Example 1 is an example that does not contain acrylate (meth)acrylate (B), which is an essential component of the present invention, but it was confirmed that the film elongation is low and processability is insufficient.
[0257] Comparative Example 2 is an example that does not contain the composite resin (A), which is an essential component of the present invention, but it was confirmed that the weather resistance is insufficient.
[0258] Comparative Example 3 is an example in which the weight average molecular weight of the acrylic (meth)acrylate (B) is lower than the lower limit of 10,000, but it was confirmed that the film elongation is low and processability is insufficient.
Claims
Claim 1 An active energy beam curable resin composition comprising a composite resin (A), an acrylic (meth)acrylate resin (B), and a photopolymerization initiator (C), wherein the composite resin (A) comprises a structural unit represented by general formula (1) and / or general formula (2), a polysiloxane segment (a1) having a silanol group and / or a hydrolyzable silyl group, and a vinyl polymer segment (a2) bonded by a bond represented by general formula (3); and the acrylic (meth)acrylate resin (B) is a reaction product of an acrylic polymer (b1) which is a polymer of a monomer mixture comprising a glycidyl group-containing (meth)acrylate monomer (x1) and two or more (meth)acrylate monomers having a glass transition temperature (Tg) of the homopolymer of 50°C or higher, and a hydroxyl group-containing (meth)acrylate monomer (x2) and / or a carboxyl group-containing (meth)acrylate monomer (x3). An active energy beam curable resin composition characterized by containing 5 to 60 parts by mass of the glycidyl group-containing (meth)acrylate monomer (x1) in 100 parts by mass of a monomer mixture, wherein the weight average molecular weight of the acrylate (meth)acrylate resin (B) is 10,000 to 70,000. (of general formulas (1) and (2), R 1 , R 2 and R 3 une, each independently, -R 4 -CH=CH2, -R 4 -C(CH3)=CH2, -R 4 -O-CO-C(CH3)=CH2, and -R 4 A group having one polymerizable double bond selected from the group consisting of -O-CO-CH=CH2 (where R 4 represents a single bond or an alkylene group having 1 to 6 carbon atoms), an alkyl group having 1 to 6 carbon atoms, a cycloalkyl group having 3 to 8 carbon atoms, an aryl group, or an aralkyl group having 7 to 12 carbon atoms. However, if the polysiloxane segment (a1) has only a structural unit represented by the general formula (1), R 1 This is a group having the above-mentioned polymerizable double bond, and in the case where the polysiloxane segment (a1) has only a structural unit represented by the general formula (2), R 2 and R 3 If at least one of the groups is having the polymerizable double bond, and the polysiloxane segment (a1) has both structural units represented by general formula (1) and general formula (2), then R 1 , R 2 and R 3 At least one of the groups is a group having the above-mentioned polymerizable double bond) (In the general formula (3), the carbon atoms constitute a part of the vinyl polymer segment (a2), and the silicon atoms bonded only to oxygen atoms constitute a part of the polysiloxane segment (a1).) Claim 2 An active energy beam curable resin composition according to claim 1, wherein the (meth)acryloyl group equivalent of the acrylic (meth)acrylate resin (B) is 300 to 3,000 g / eq. Claim 3 An active energy beam curable resin composition according to claim 1, wherein the mass ratio (A / B) of the composite resin (A) and the acrylate (meth)acrylate resin (B) is 2 / 98 to 90 / 10. Claim 4 An active energy beam curable resin composition according to claim 1, wherein the content of the polysiloxane segment (a1) in the total resin component is 2 to 55 mass%. Claim 5 A cured film of an active energy beam curable resin composition as described in any one of claims 1 to 4. Claim 6 Article having a hardened film as described in paragraph 5. Claim 7 delete
Citation Information
Patent Citations
Ultraviolet-curable resin composition, ultraviolet-curable coating, and coated article
JP2006328354A
Active energy ray curable composition and coating film
JP2013199522A
Cured product, and production method therefor
JP2016017151A
Method for manufacturing composite fine particle
JP2007224312A
Method for manufacturing coated building material and obtained coated building material
JP2021013887A
